Bridging Distance Learning: Insights into Synchronous and Asynchronous Approaches for Enhancing English Speaking Skills - Zainuddin, Dini Apriani; Patak, Andi Anto (Tamaddun Life, 2024)
This study investigates the perspectives of teachers and students on the effectiveness of synchronous and asynchronous learning approaches in enhancing English speaking skills, focusing on grammar, vocabulary, pronunciation, fluency, and comprehension. Conducted in a junior high school setting in Indonesia, the research employs a qualitative descriptive method, collecting data through semi-structured interviews with three teachers and three students. Thematic analysis was applied to explore patterns and themes in participants' responses. The findings reveal that synchronous learning fosters real-time interaction, enhancing vocabulary acquisition and comprehension through immediate feedback. However, challenges such as grammatical inaccuracies and low student confidence persist. Asynchronous learning provides students with the flexibility to refine their tasks, improving grammar, vocabulary, and pronunciation, but lacks the immediacy of feedback essential for addressing comprehension and pronunciation errors in real-time. The study underscores the complementary nature of these modalities, highlighting the potential of a blended or bichronous approach to optimize learning outcomes. The research contributes to the discourse on distance education by offering practical insights into integrating synchronous and asynchronous learning for language instruction. Recommendations include strategic lesson planning, teacher training in digital tools, and addressing infrastructural challenges to ensure equitable access. The study also suggests further exploration of bichronous learning models and their impact on long-term language proficiency. This research provides valuable guidance for educators and policymakers aiming to enhance English language education in digital and hybrid learning environments.